2005
DOI: 10.1093/hmg/ddi154
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptor 4 variant D299G is associated with susceptibility to age-related macular degeneration

Abstract: Age-related macular degeneration (AMD) is a genetically heterogeneous disease that leads to progressive and irreversible vision loss among the elderly. Inflammation, oxidative damage, cholesterol metabolism and/or impaired function of retinal pigment epithelium (RPE) have been implicated in AMD pathogenesis. We examined toll-like receptor 4 (TLR4) as a candidate gene for AMD susceptibility because: (i) the TLR4 gene is located on chromosome 9q32-33, a region exhibiting evidence of linkage to AMD in three indep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
116
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(118 citation statements)
references
References 61 publications
2
116
0
Order By: Relevance
“…The presence of cholesterol and CE deposits in the Bruch's membrane of AMD eyes (9,10) and the correlation of genetic variations in cholesterol transporters with AMD susceptibility (12,13) point to an age-related alteration in cholesterol homeostasis in the RPE that may contribute to AMD progression. In this context, it is noteworthy that cholesterol and CE deposits in the Bruch's membrane are thought to originate from the RPE, including incompletely processed OS and additional sources such as the RPE itself (9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of cholesterol and CE deposits in the Bruch's membrane of AMD eyes (9,10) and the correlation of genetic variations in cholesterol transporters with AMD susceptibility (12,13) point to an age-related alteration in cholesterol homeostasis in the RPE that may contribute to AMD progression. In this context, it is noteworthy that cholesterol and CE deposits in the Bruch's membrane are thought to originate from the RPE, including incompletely processed OS and additional sources such as the RPE itself (9).…”
Section: Discussionmentioning
confidence: 99%
“…Apolipoproteins, cholesterol and cholesteryl esters (CE) are abundant in both drusen (lipid-protein aggregates in the Bruch's membrane) and other subRPE deposits in AMD eyes (9)(10)(11), suggesting compromised cholesterol homeostasis in the RPE. Moreover, cardiovascular disease and allelic variants in apolipoprotein E and ATP-binding cassette protein A1 (ABCA1) have been linked to AMD susceptibility in humans (12,13).…”
Section: Proteins Involved In Cholesterol Traffickingmentioning
confidence: 99%
“…Chronic retinal inflammation in humans is expected to cause iron overload within the retina, but whether such effects have any relevance to the pathogenesis of age-related macular degeneration remains to be seen. It is interesting to note that genetic variations in genes involved in inflammation and oxidative stress, including the Toll-like receptor-4 [43], have been implicated in the pathogenesis of age-related macular degeneration [44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…Although single nucleotide polymorphisms of TLR3 and TLR4 have been reported to regulate AMD susceptibility (20,36), several conflicting reports indicating a weak relationship between AMD and these TLRs accentuate the need for studies other than single nucleotide polymorphism analyses (37)(38)(39)(40)(41)(42). To examine the biological role of TLRs in retinal degeneration, we performed gene expression analyses of TLR-signaling molecules in the eyes of Rdh8…”
Section: Toll-like Receptors Are Involved In Age-related Retinal Degementioning
confidence: 99%
“…Genes encoding complement factor H (7-14), HtrA serine peptidase 1 (HTRA1) (60 -63), and complement components 2 and 3 (C2 and C3) (15,16) were reported to predispose to AMD, and both human and mouse studies have demonstrated complement deposition at AMD lesions (64 -66). In addition, the F412L polymorphism of TLR3 (20) and the D299G of TLR4 (36) have been reported, but these findings were refuted by multiple groups (37)(38)(39)(40)(41)(42). Thus, there is an emerging consensus that innate immunity plays an important role in the pathogenesis of AMD.…”
Section: Rdh8mentioning
confidence: 99%